Step-by-step explanation:
![{q}^{2} - 12q + 36 \\ = {q}^{2} - 6q - 6q + 36 \\ = q(q - 6) - 6(q - 6) \\ \huge \red{ \boxed {= (q - 6)(q - 6) }}\\ is \: the \: factored \: form.](https://tex.z-dn.net/?f=%20%7Bq%7D%5E%7B2%7D%20%20-%2012q%20%2B%2036%20%5C%5C%20%20%3D%20%20%7Bq%7D%5E%7B2%7D%20%20-%206q%20-%206q%20%2B%2036%20%5C%5C%20%20%3D%20q%28q%20-%206%29%20-%206%28q%20-%206%29%20%5C%5C%20%20%20%5Chuge%20%5Cred%7B%20%5Cboxed%20%7B%3D%20%28q%20-%206%29%28q%20-%206%29%20%7D%7D%5C%5C%20is%20%5C%3A%20the%20%5C%3A%20factored%20%5C%3A%20form.)
Answer:
$16.03
Step-by-step explanation:
Answer:-5.8
Explanation:4.5-8.3=-3.8 -3.8-2=5.8
Answer:
A. SAS
Step-by-step explanation:
Since the marked angle is between the marked sides, and the corresponding sides are marked as congruent, the two triangles are congruent by SAS (side angle side).